Bringing Prebiotic Nucleosides and Nucleotides Down to Earth. Issue 45 (15th September 2016) - Fiore, Michele; Strazewski, Peter
Abstract : There may be more than one way leading to RNA : Recent discoveries in the synthesis of nucleoside and nucleotide precursors are described and put into the wider context of prebiotic systems chemistry. Mixing Butlerow's carbohydrate precursors with Traube's 5‐formylaminopyrimidines has led to the formation of prebiotic purine nucleosides whereas the mixing of 5‐phosphoribose with barbituric acid and melamine gave supramolecular fibers from stacks of Whitesides' rosettas.